A journey through the woods. - Valbuena, Joyce; Lauron, Ma. Theresa N.; Dongeto, Romeo C.; Santos, Carlo (AV032., 1997)
A soft animated feature about a young boy's camping trip to the woods. Focuses on children's role in the protection of the environment.